The marketer-a complex specialist, a man of concept, decision and action - Nicolae Al. Pop; Anca-Daniela Vlădoi (Amfiteatru Economic Journal, 2009)
Over the last fifty years, the theory and practice of contemporary marketing have been influenced by the focus of its applicative approach over a major landmark of the business world. A short characterization of its different orientations, from consumer oriented marketing to holistic marketing, can only lead to the conclusion regarding the formative complexity of the specialist working in this field. The profile of this specialist is to be understood in such a manner as to have a competitive response, based on the decisions he/she must make, in random and undetermined decisional circumstances. His/her inclusion in lucrative activities, the level of financial motivation and the requests to be confronted with are analyzed in the context of the working force market in Romania. The formative role played by the upper echelon of the Romanian school over future marketers is also emphasized.
Keywords: M31; 330; holistic marketing; marketer; key account manager; Romanian academics marketing